Call for Submissions. Special Issue - July 2018: Patient & Family Experience in Children's Hospitals and Pediatric Care - Patient Experience Journal (The Beryl Institute, 2017)
Patient Experience Journal (PXJ) is excited to announce a call for submission for its special issue scheduled for July 2018 on the topic of patient & family experience in children's hospitals and pediatric care. This special issue is open to all authors conducting cutting-edge research, implementing innovative practices or with powerful experiences to share around efforts in either children's hospitals or pediatric care. It is encouraged that articles submitted deal directly with efforts in those care settings. The issue will look for pieces that address evidence-based efforts at improvement, practices that have impact on outcomes or stories that reflect the true meaning and opportunity in a positive patient & family experience in pediatrics. It will provide an opportunity to highlight accomplishments, reveal new findings and contribute to the literature aimed at improving results. The deadline for submissions for this special issue is March 1, 2018. You can begin the submission process here: http://bit.ly/PXJ_Submit.